2015
DOI: 10.1007/s12094-014-1263-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of RalB in the effect of geranylgeranyltransferase I on glioma cell migration and invasion

Abstract: These findings suggest that RalB might be one of the targets for facilitating the invasive phenotype of malignant gliomas induced by GGTase-I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Surprisingly, very few data exist about the importance of Ral GTPases in GBM. Our results are consistent with a previous report showing that the knockdown of RalB decreases the invasiveness of human GBM cell lines .…”
Section: Discussionsupporting
confidence: 93%
“…Surprisingly, very few data exist about the importance of Ral GTPases in GBM. Our results are consistent with a previous report showing that the knockdown of RalB decreases the invasiveness of human GBM cell lines .…”
Section: Discussionsupporting
confidence: 93%
“…However, little is known about the role of Ral-GTPases in human malignant gliomas. The importance of geranylgeranyltransferase I (GGTase-I) in cancer progression and metastasis through membrane-targeting of Ral GTPases has been highlighted [ 20 ]. Other works have showed that overexpression of Ral-BP1 is associated with glioma grade and poor survival [ 21 ] and that Ral-BP1 knockdown reduces invasiveness, increases chemosensitivity to TMZ, and enhances the autophagy flux in these cells [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…RALA and RALB were shown to be involved in both mediating the inhibition of anchorage-independent growth and cell cycle progression in these cells. The importance of RALB in mediating the growth inhibition effect of GGTIs was also confirmed in other cancer types like glioma and squamous cell carcinoma (Hamada et al, 2011;Song et al, 2015). One potential problem with targeting GGTase is that many other RAS family members are also substrates for GGTase I, targeting of which might result in normal tissue toxicity.…”
Section: Targeting Ral Localizationmentioning
confidence: 84%